PENGEMBANGAN MEDIA POP UP BERBASIS AUDIO VISUAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATERI SIKLUS AIR BAGI SISWA SEKOLAH DASAR - Gabriella Finna; Yudha Popiyanto; Reza Syehma Bahtiar (Jurnal Inovasi Penelitian, 2022)
Basic concept education in applying science according to students' abilities to achieve learning objectives. The world is currently being hit by the Coronavirus Disease (Covid-19). The government changed several learning systems, various efforts were made to prevent Covid-19, especially in the field of education. The development of pop up media is recommended in learning to explain in detail the material that will be delivered to students. Pop up media is developed in audio-visual based water cycle material. In this study, the objectives are (1). Producing appropriate audio-visual-based pop-up media to improve critical thinking skills on water cycle material for fifth grade students of UPT SD Negeri 62 Gresik. (2). produce an effective audio-visual-based pop-up media to improve critical thinking skills on water cycle material for fifth grade students of UPT SD Negeri 62 Gresik. This study uses the ADDIE development method and quantitative data collection obtained from test results (pre-test and post-test), expert validation (material experts and media experts). The results obtained are as follows, that the development of audio-visual-based pop-up media can improve critical thinking skills in the water cycle material for fifth grade students. This can be seen through the pre-test with a value of 1580 and an average value of 79. The post-test got the number of 1930 and the average value of 96,5. The difference between the increase in the scores of the pre-test and post-test students is 17,5